Digital Graffiti: Ekspresi Kreatif Di Lingkungan Digital - Rachman, Anung (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2012)
Digital technology is enabling graffiti art to take on new forms, creating an alternative for the artist in making art work. Few attempts, though, have been made to integrate classical expression of graffiti into virtual space, and digital graffiti artists are still adjusting himself to the Internet and to digital tool. This paper describes a variety of graffiti form movement from the streets to the virtual, from the technology used, classification, until coding. Various advantages presented of digital graffiti, more practical, more diverse, and reach out to all corners of the world. We aim to enrich digital art culture, drawing inspiration from the art form and culture surrounding graffiti, making it visible to mainstream Internet user and creative expression.Â keyword: digital graffiti, digital environment, technology, internet